Shifting Inheritance Patterns in the Minangkabau Tribe in Negeri Sembilan, Malaysia - Ismail, Ismail; Nofiardi, Nofiardi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
In the Minang Urang Darek Luhak Nan Tigo and Urang Rantau Negeri Sembilan Malaysia communities, inheritance is passed down to nieces based on matrilineal practices. They hold a significant role in the tradition, following the sumandocustom, and the offspring belong to their mother's tribe. This study seeks to ascertain whether the practice of inheriting heirlooms in the Minang Urang Darek Luhak Nan Tigo and Urang Rantau Negeri Sembilan Malaysia communities is still in accordance with traditional customs or if it has started to deviate from prior norms. This study employed an anthropological methodology, utilizing in-depth interviews. The findings suggest that the father has taken on the position of an expert and protector, while the mother's involvement is limited to customary events. In contrast to the residents of Negeri Sembilan who continue to reside in the village, there are some who have relocated outside of Negeri Sembilan. The inhabitants of Negeri Sembilan who reside in their native region continue to firmly uphold traditional customs, whilst those that relocate outside of Negeri Sembilan have resettled in their paternal hometowns. The inheritance of ancestral property has altered in accordance with the changing role of the mother. In the past, it was customary for ancestral property to be inherited by nieces. However, there has been a shift in this practice, with some individuals now choosing to pass down their ancestral land to their own children. As a result, many ancestral lands in Negeri Sembilan have been left abandoned as people seek livelihoods in new locations.